Causal association between colorectal cancer and Alzheimer’s disease: a bidirectional two-sample mendelian randomization study - Yuan, Chunsheng; Liu, Saisai; Yang, Kezhen; Xie, Feiyu; Li, Yinan; Guo, Yantong; Zhao, Wenjun; Zhang, Jincheng; Cheng, Zhiqiang (Frontiers in Genetics, 2024)
Colorectal cancer and Alzheimer's disease are both common life-threatening diseases in the elderly population. Some studies suggest a possible inverse relationship between colorectal cancer and Alzheimer's disease, but real-world research is subject to many biases. We hope to clarify the causal relationship between the two through a bidirectional two-sample Mendelian randomization study.In our study, we used genetic summary data from large-scale genome-wide association studies to investigate the relationship between colorectal cancer and Alzheimer's disease. Our primary analysis employed the inverse-variance weighted method and we also used complementary techniques, including MR-Egger, weighted median estimator, and Maximum likelihood. We applied simex adjustment to the MR-Egger results. We also utilized the MRlap package to detect potential sample overlap and its impact on the bias of the results. In addition, we performed several sensitivity and heterogeneity analyses, to ensure the reliability of our results.This is a provisional file, not the final typeset articleThe combined effect size results of the inverse-variance weighted method indicate that colorectal cancer may decrease the incidence of Alzheimer's disease, with an odds ratio (OR) of 0.846 (95% CI: 0.762-0.929). Similar results were observed using other methods such as MR-Egger, weighted median estimator, and Maximum likelihood. On the other hand, Alzheimer's disease may slightly increase the incidence of colorectal cancer, with an OR of 1.014 (95% CI: 1.001-1.027). However, the results of one subgroup were not significant, and the results from MRlap indicated that sample overlap introduced bias into the results. Therefore, the results of the reverse validation are not reliable. The results of these statistics were further validated by MR-PRESSO, funnel plots, leave-one-out analyses, Cochran's Q, demonstrating the reliability of the findings.According to the findings of this Mendelian randomization study, there appears to be a causal association between colorectal cancer and Alzheimer's disease. These results could have important implications for clinical practice in terms of how colorectal cancer and Alzheimer's disease are treated. To better understand the relationship between these two diseases, more research and screening are needed in clinical settings.